PERANAN AKURASI SISTEM KOMPUTER HOTEL DI FRONT OFFICE DEPARTEMENT DALAM MENINGKATKAN KEPUASAN TAMU DI THE BALAVA HOTEL MALANG - fitria earlike anwar sani (Universitas Merdeka Malang, 2016)
Front Office is where the provision of information for guests were in the hotel from arranging their departure, including managing payments during their stay at the hotel. To facilitate the work of Front Office, the hotel uses a system called the Emerald System. System as one of the leading framework for managing information technology control serves to bring together all the needs of management by bridging existing dividing business risks, control needs and technical issues. According to the results of questionnaires computer system in The Balava Hotel still not accurately be seen from the number of respondents who answered